Magnetic resonance safety and compatibility of tantalum markers used in proton beam therapy for intraocular tumors: A 7.0 Tesla study. Issue 4 (10th November 2016) - Oberacker, Eva; Paul, Katharina; Huelnhagen, Till; Oezerdem, Celal; Winter, Lukas; Pohlmann, Andreas; Boehmert, Laura; Stachs, Oliver; Heufelder, Jens; Weber, Andreas; Rehak, Matus; Seibel, Ira; et al.
Abstract : Purpose: Proton radiation therapy (PRT) is a standard treatment of uveal melanoma. PRT patients undergo implantation of ocular tantalum markers (OTMs) for treatment planning. Ultra‐high‐field MRI is a promising technique for 3D tumor visualization and PRT planning. This work examines MR safety and compatibility of OTMs at 7.0 Tesla. Methods: MR safety assessment included deflection angle measurements (DAMs), electromagnetic field (EMF) simulations for specific absorption rate (SAR) estimation, and temperature simulations for examining radiofrequency heating using a bow‐tie dipole antenna for transmission. MR compatibility was assessed by susceptibility artifacts in agarose, ex vivo pig eyes, and in an ex vivo tumor eye using gradient echo and fast spin‐echo imaging. Results: DAM (α < 1 °) demonstrated no risk attributed to magnetically induced OTM deflection. EMF simulations showed that an OTM can be approximated by a disk, demonstrated the need for averaging masses of mave = 0.01 g to accommodate the OTM, and provided SAR0.01g, maximum = 2.64 W/kg (Pin = 1W) in OTM presence. A transfer function was derived, enabling SAR0.01g estimation for individual patient scenarios without the OTM being integrated. Thermal simulations revealed minor OTM‐related temperature increase (δT < 15 mK). Susceptibility artifact size (<8 mm) and location suggest no restrictions for MRI of the nervus opticus. Conclusion: OTMs are not a per se contraindication for MRI. Magn Reson Med 78:1533–1546, 2017. © 2016 International Society for Magnetic Resonance in Medicine.